Executing innovation : expert solutions to everyday challenges. - Harvard Business School. Press (Boston, Mass. : Harvard Business Press, 2009)
"Ideas are not enough: successful innovation requires real-life execution from start to finish. This book helps you move your initiatives forward by showing you how to: Develop a motivating vision statement; Identify stakeholders and build a strong business case; Overcome explicit and hidden resistance to change; and Maintain the momentum around your project."--BOOK JACKET.
Mentor s Message: Why Executing Innovation Matters -- Executing Innovation: The Basic -- Why Innovate? -- Step 1. Develop an Inspiring Vision -- Step 2. Identity Stakeholders -- Step 3. Cultivate Your Support Network -- Step 4. Build Your Business Case -- Step 5. Communicate with Your Stakeholders -- Step 6. Manage Resistance -- Step 7. Stay Passionate About Your Innovation -- Tips and Tools -- Tools for Executing Innovation -- Test Yourself -- To Learn More.
Includes bibliographical references (pages 93-94).
Description based on print version record.
Keywords: Technological innovations; Creative ability in business; Creative ability in business; Technological innovations; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books